EFFICIENCY OF FINANCIAL CONTROL IN PROJECT MANAGEMENT: A COMPARATIVE ANALYSIS OF TRADITIONAL AND AGILITY METHODOLOGIES - Elnaza Kassymkhanova (Modern American Journals, 2025)
The article is devoted to the study of the role of financial control in project management, with an emphasis on its implementation within the framework of traditional (Waterfall, PRINCE2) and flexible (Agile, Scrum, Kanban) methodologies. A comparative analysis of financial monitoring tools, supported by empirical data and visual representations, is conducted. The conditions that contribute to achieving an optimal compromise between budget transparency and adaptability of project management when choosing the appropriate methodology are determined.
Keywords: Financial control, project management, Waterfall, Agile, Scrum, budgeting, cost control.